RISK FACTORS OF CONGENITAL ANOMALIE AT HAJJ ADAM MALIK GENERAL HOSPITAL AND UNIVERSITY OF NORTH SUMATERA HOSPITAL IN 2017-2019. - Refa Perdana Mukti; Gema Nazri Yanni (Talenta Publisher, 2020)
Background. Congenital abnormalities or congenital abnormalities are abnormalities that have existed since birth that can be caused by genetic and non genetic factors. The study of congenital abnormalities is called dysmorphology. Congenital abnormalities are one of the biggest contributors to death and morbidity in neonates, infants, and children. There were 7.9 million cases of congenital abnormalities and 3.3 million premature deaths due to congenital abnormalities in the world in 2013. In Southeast Asia it is estimated that cases of congenital abnormalities numbered 1,946,606 cases each year in 2013 according to WHO. In 2018, more than 8 million babies worldwide are born every year with congenital abnormalities. In the United States nearly 120,000 babies are born with congenital abnormalities each year. The cause of fetal congenital abnormalities due to genetic and non-genetic factors. Single gene mutations, balance disorders due to chromosomal abnormalities, and multifactorial abnormalities are included in genetic factors. Non-genetic factors can be caused by teratogen drugs (drugs, chemicals, infections, and maternal diseases that affect the fetus) and radiation. There are 5 risk factors that influence the occurrence of fetal congenital abnormalities, namely genetic, socioeconomic and demographic factors, environment, infection, and nutritional status. Aim. To determine the risk factors for congenital abnormalities in newborns at the Haji Adam Malik General Hospital and the University Hospital of North Sumatra in 2017-2019. Method. The design used by researchers uses a cross-sectional approach. The sample used was Patients with Congenital Abnormalities who were in the Human Rights Hospital and USU Hospital in 2017-2019. Result. The most influential risk factors for fetal abnormalities are maternal age, disease history, infectious history, and poor nutritional status. There are no results that can prove that the history of pregnancy affects the occurrence of fetal congenital abnormalities.